2009
DOI: 10.1017/s0043933909000004
|View full text |Cite
|
Sign up to set email alerts
|

Use of bitter vetch ( vicia ervilia) as a feed ingredient for poultry

Abstract: The increasing costs of conventional feedstuffs like corn, soybean meal and fish meal for poultry diets is pushing the need to find less expensive alternatives. Bitter vetch (Vicia ervilia) is an ancient grain legume crop that originated in the Mediterranean region, but now can be found in many countries around the world. It has many favourable characteristics, such as having high yields and being resistant to drought and insects. Bitter vetch (BV) is a good source of metabolisable energy (13.57 MJ/ kg), prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Fax: 00903524376209. drought and insects and good energy and protein content that make it a potential economically useful source for poultry diets. The crop is easy to cultivate and harvest and can be grown on very shallow, alkaline soils where other grains such as corn and soybean do not grow successfully (Sadeghi et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Fax: 00903524376209. drought and insects and good energy and protein content that make it a potential economically useful source for poultry diets. The crop is easy to cultivate and harvest and can be grown on very shallow, alkaline soils where other grains such as corn and soybean do not grow successfully (Sadeghi et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Jasińska and Kotecki (1998) reported crude protein content in broad bean seed was determined more by genetic factors than by the ecological condition. High-protein grains are low-cost sources for livestock (Sadeghi et al 2009). Tufatelli et al (2012) reported feeding broad bean seeds in a lactation diet for cattle supports performance similar to cattle diet traditional soybean meal.…”
Section: Resultsmentioning
confidence: 99%
“…Vetch can be grazed by animals as fresh forage (Haddad, 2006) or can be cut and preserved as hay and silage (Abdullah et al, 2010). Vetches hay can be used as a protein supplement, and their grains serve as energy and protein sources in the rations of ruminants and non-ruminants (Sadeghi et al, 2009). The potential of narbon vetch for grain production as livestock feed is greater than other vetch species, and the grain contains tannin and trypsin inhibitors that is directly affecting its efficiency of feed (Berger et al, 2002;Larbi et al, 2010), in general narbon vetch is cultivated for grain production (Buyukburc and Iptas, 2001).…”
Section: Introductionmentioning
confidence: 99%